DESTINY OF INJUSTICE IN WILLIAM LANDAY’S NOVEL DEFENDING JACOB - Sudwintari Sudwintari; Sri Wulan (JOURNAL OF LANGUAGE, 2019)
This study discusses Protagonist’s Destiny of Injustice in William Landay’s novel Defending Jacob. This study adopts much of Gulen’s theory about destiny and injustice which is quoted by Haderi. Then, this research is completed by adopting descriptive qualitative method. There are three forms of the protagonist’s destiny of injustice. They are being accused of murder, being dismissed from school, and being isolated. The findings of the analysis are the protagonist has got many things for his injustice. The protagonist really suffers the injustice. The protagonist has passed several trials to be declared not guilty and free. It can be found clearly that the protagonist in this novel meets his destiny of injustice. At last, fortunately the protagonist is free from the accusation because the murderer has been revealed. The ending of the story shows that the protagonist can be free from the accusation because actually the one who kills his classmate is a pedophile.